Pengaruh Celebrity Endorsement Dan Online Consumer Review Terhadap Minat Beli Produk Eat Sambel Di E-commerce Shopee - Firdausi, Vanesa Rizkia; Giri, Refi Rifaldi Windya (eProceedings of Management, 2024)
In today's digital era, social media plays a significant role in influencing consumer purchase intentions. In the digitalera, marketing through celebrities has become an important strategy in e-commerce, including for Eat Sambalproducts on Shopee. This marketing is considered effective in enhancing product image and quickly attractingconsumers. The success of celebrity marketing lies not only in visual appeal but also in credibility and social influencethat shape consumer perceptions and purchase intentions. Online consumer reviews are also crucial in increasingpurchase interest as they help consumers learn more about the product. This study aims to investigate the influenceof celebrity endorsement and online consumer reviews on the purchase intention of Eat Sambal products on Shopee,with variables of celebrity credibility, celebrity appeal, and online consumer reviews mediated by attitude, brandloyalty, brand awareness, and e-WoM towards purchase intention. Data were collected through online surveys andanalyzed using SEM with SmartPLS4. The results of the study show that celebrity credibility, and online consumerreviews significantly influence consumer attitudes, which then affect brand loyalty, brand awareness, and e-WoM.This research provides insights for companies regarding effective digital marketing strategies through celebrityendorsement and online consumer reviews in e-commerce. Keywords-celebrity endorsement, online consumer review, consumer perception, purchase intention, digitalmarketing.